1992
DOI: 10.1029/91ja02376
|View full text |Cite
|
Sign up to set email alerts
|

Distribution in magnetotail of O+ ions from cusp/cleft ionosphere: A possible substorm trigger

Abstract: The transport of O+ ions from the cusp/cleft ionosphere to the magnetotail during highly disturbed times was determined by computing the guiding‐center trajectories of the ions to a distance of 6 RE from the ionosphere and the full‐motion trajectories at later times. Case histories were tallied in six planes perpendicular to the XGSM axis, three planes perpendicular to the YGSM axis, and in the center plane of the tail. At various times relative to the enhancement of the convection electric field, the followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
46
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(49 citation statements)
references
References 28 publications
3
46
0
Order By: Relevance
“…Theoretical and modelling studies suggested an impact of O + ions on plasma sheet reconnection (Baker et al, 1982;Shay and Swisdak, 2004;Brambles et al, 2010). Some studies indicate that O + ions can trigger substorms (Cladis and Francis, 1992;Yu and Ridley, 2013), and others that sawtooth events may be induced by ionospheric outflow (Brambles et al, 2011;Ouellette et al, 2013). Observational studies have not really been able to confirm nor refute this (e.g.…”
Section: Introductionmentioning
confidence: 92%
“…Theoretical and modelling studies suggested an impact of O + ions on plasma sheet reconnection (Baker et al, 1982;Shay and Swisdak, 2004;Brambles et al, 2010). Some studies indicate that O + ions can trigger substorms (Cladis and Francis, 1992;Yu and Ridley, 2013), and others that sawtooth events may be induced by ionospheric outflow (Brambles et al, 2011;Ouellette et al, 2013). Observational studies have not really been able to confirm nor refute this (e.g.…”
Section: Introductionmentioning
confidence: 92%
“…The acceleration of ionospheric ions and their transport into the plasma sheet and ring current have been investigated by particle tracing calculations for a number of years (Green and Horwitz 1986;Sauvaud and Delcourt 1987;Delcourt et al 1989Delcourt et al , 1990Cladis and Francis 1992;Peroomian 1994;Peroomian andAshour-Abdalla 1995, 1996;Moore and Delcourt 1995;Ebihara et al 2006;Yau et al 2012). More recently, Peroomian et al (2006Peroomian et al ( , 2007Peroomian et al ( , 2011aPeroomian et al ( , 2011b have investigated the access and energization of ionospheric ions to the magnetotail during geomagnetic storms by using LSK particle tracing simulation using time-dependent electric and magnetic fields of individual storm events.…”
Section: Simulating the Ion Historymentioning
confidence: 99%
“…Observations during active times have shown that O + can become the dominant component of the plasma sheet [Peterson et al, 1981;Kistler et al, 2005]. Several studies have indicated that O + could influence the substorm process by changing the growth phase [Daglis et al, 1990] and affecting the initiation mechanism [Baker et al, 1982;Cladis and Francis, 1992;Lakhina, 1995]. However, the global consequences of this plasma on the magnetosphere-ionosphere system are difficult to evaluate observationally [Lotko, 2007].…”
Section: Introductionmentioning
confidence: 99%